2005
DOI: 10.1021/jp050092k
|View full text |Cite
|
Sign up to set email alerts
|

An Infrared Investigation of the (CO2)n- Clusters:  Core Ion Switching from Both the Ion and Solvent Perspectives

Abstract: The (CO2)n- clusters are thought to accommodate the excess electron by forming a localized molecular anion, or "core ion", solvated by the remaining, largely neutral CO2 molecules. Earlier studies interpreted discontinuities in the (CO2)n- photoelectron spectra to indicate that both the CO2- and C2O4- species were present in a size-dependent fashion. Here we use vibrational predissociation spectroscopy to unambiguously establish the molecular structures of the core ions in the 2 < or = n < or = 17 size range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
76
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 33 publications
7
76
0
2
Order By: Relevance
“…In addition, the results peripherally reveal the signature of another core anion for n ) 1-4, assigned to the ONNNO -structure first proposed by Hiraoka et al 16 and characterized spectroscopically by Continetti and co-workers. 17 We examine the coexistence of the NO -and ONNNO -cluster cores under stepwise solvation by N 2 O and interpret the findings in terms of gradual core-shifting (rather than abrupt core-switching [18][19][20][21] attributed to the interplay between the relative stabilities of the NO -and ONNNO -anions and the preferential solvation of the smaller NO -core.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results peripherally reveal the signature of another core anion for n ) 1-4, assigned to the ONNNO -structure first proposed by Hiraoka et al 16 and characterized spectroscopically by Continetti and co-workers. 17 We examine the coexistence of the NO -and ONNNO -cluster cores under stepwise solvation by N 2 O and interpret the findings in terms of gradual core-shifting (rather than abrupt core-switching [18][19][20][21] attributed to the interplay between the relative stabilities of the NO -and ONNNO -anions and the preferential solvation of the smaller NO -core.…”
Section: Introductionmentioning
confidence: 99%
“…The groups of Johnson and of Nagata found that the VDEs of CO 2 cluster anions show pronounced discontinuities [104,105] at cluster sizes n ¼ 6 and 14 (see Figure 6). The infrared spectra of (CO 2 ) À n cluster ions reported jointly by the Johnson and Weber groups show similarly abrupt changes for the same cluster sizes [107], although the changes around n ¼ 6 are more gradual (see Figure 6). These two independent observations show unambiguously that the charge carrying species changes as a function of cluster size, and they allow us to draw structural conclusions on the nature of the core ions as well.…”
Section: 2mentioning
confidence: 61%
“…This peak Figure 6. Size evolution of the vertical detachment energies (left, adapted from [105] with permission from Elsevier) and vibrational spectra (right, reprinted with permission from [107], copyright (2005) American Chemical Society) for (CO 2 ) À n anions. The dashed line is meant to guide the eye.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared(IR) spectroscopic study of stretching frequency vibrations with alteration in sizes have been done. [16][17][18] Theoreticians have tried to do quantum chemical calculations at various levels of theory like DFT, MP2, etc. [19][20][21][22] to arrive at the stretching frequency values that experimentalists have obtained.…”
Section: Introductionmentioning
confidence: 99%